Experiences of Post-treatment Patients with Systemic Lupus in Indonesia - Mohamad Judha; Elizabeth C. Baua; Josephine D. Lorica (The Malaysian Journal of Nursing (MJN), 2022)
Background: Indonesia is currently associated with lupus disease that tends to increase in number, based on data from the Lupus Indonesia Foundation. About 90% of women are with lupus. Most women with reproductive status are inactive, and most want to have basic needs fulfillment disorders. As a result of the changes that arise and because of the long healing process and the disruption basic needs can cause prolonged sadness for the sufferer. Aims: To develop the concept of nursing theory through research from participants suffering from Lupus. Methods: This research is qualitative research to explore the experience of participants looking for the meaning of life. The study consisted of nine participants with purposive samples. Results: In this study data was obtained nine themes, among others: (1) Responses consisted of experience with Lupus disease, (2) Types of support obtained from the environment 3) Discrimination experienced (4) Efforts made to achieve recovery, (5) Ability to recognize signs and symptoms, (6) Changes in basic needs, and Effects of Lupus on activities (7) The effect of using drugs (8) Health services and resources(9) Changes in values, and beliefs. Conclusion: The results of the study contained the response of patients in dealing with Lupus disease related to physical activity, psychological and environmental changes as well as changes in the value, beliefs, and beliefs of Lupus sufferers Recommendation: The results suggest that healthcare workers must perform comprehensive care. Education awareness must be provided also. Holistic nursing care to be conducted. Future researchers must consider increasing the gender variation of participants in order to obtain a variety of themes.